2020
DOI: 10.1007/s42452-020-2633-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti-precursor concentration and annealing temperature on structural and morphological properties of TiO2 nano-aerogels synthesized in supercritical ethanol

Abstract: TiO 2 nano-aerogels are elaborated by using acid-modified sol-gel approach from titanium tetra isopropoxide under supercritical drying conditions of ethanol. The effects of Ti-precursor concentration and annealing temperature on structural and morphological properties of TiO 2 nanoparticles are investigated by XRD, infrared spectroscopy, SEM and specific surface area measurements. It was found, from XRD analysis, that pure anatase phase is obtained for the aerogels synthesized with various precursor concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Besides shape, the surface area and pore volume can be modified by the precursor concentration. [30] In our case, with the variation of TTIP concentration, great changes occurs in the morphology. The reaction temperature and time is the same for these samples, therefore, such change in shape can only be induced by the kinetics.…”
Section: Influence Of the Concentration Of Ttipmentioning
confidence: 48%
See 1 more Smart Citation
“…Besides shape, the surface area and pore volume can be modified by the precursor concentration. [30] In our case, with the variation of TTIP concentration, great changes occurs in the morphology. The reaction temperature and time is the same for these samples, therefore, such change in shape can only be induced by the kinetics.…”
Section: Influence Of the Concentration Of Ttipmentioning
confidence: 48%
“…As reported in literature [28,29], more TTIP benefits the crystalline structure of TiO2. Djouadi et al [30] reported that the rise of sol concentration could affect the TiO2 cell parameters. The precursor concentration can also affect the morphology.…”
Section: Influence Of the Concentration Of Ttipmentioning
confidence: 99%
“…Ti-O-Mg bond formation through Mg doping is believed to hinder grain growth, resulting in smaller crystallites [27]. Other parameters, such as micro-strain, dislocation density, lattice parameters, lattice volume, and dspacing [38,39] were determined and tabulated in table 2.…”
Section: Impact Of Mg On Tio 2 Crystal Structural Propertiesmentioning
confidence: 99%
“…The results of ATR spectroscopy are shown in Figure 3. In this characterization, two absorption bands can be identified that correspond to the Ti-O-Ti bond when there is an incidence of light with a wave number of 734 cm −1 [43,46] and a bond of Si-O for a wavenumber of 1106 cm −1 . An additional signal at 1240 cm −1 can be observed in For the three compact TiO 2 test samples that were deposited under the same sputtering atmosphere conditions (10 O 2 /40 Ar) under normal sputtering conditions, varying only the deposit power to 100, 120, and 140 W. The diffraction patterns showed a diffraction peak at an angle 2θ = 24.8 • as the principal maximum, and this peak corresponds to the signal of the plane (101) of the structure tetragonal anatase typical of TiO 2 .…”
Section: Compact Tio 2 Test Layersmentioning
confidence: 99%